ANALISIS TINDAK TUTUR ILOKUSI DIREKTIF DALAM PERISTIWA TUTUR RAPAT DI MAN 3 PANDEGLANG TAHUN AJARAN 2019/2020 - Resti Nurul Aeni (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study is (1) to calibrate and explain the form of directive speech in the event of a service meeting in the school environment man 3 Pandeglang school year 2019/2020; (2) classify and explain the function of the directive in the speech of the office meeting in the school environment man 3 Pandeglang school year 2019/2020; and (3) classify and explain the implications in the event of a service meeting in the school environment MAN 3 Pandeglang school year 2019/2020. This research that became the object of the study is a meeting at MAN 3 Pandeglang. This research is a descriptive qualitative study. In this study, it was conducted using contextual analysis methods. Based on the results of the study there are types, function of speech directive and implications generated by the action of the directive as much as 52 data, namely the action of the directive of the request including the function of requesting 1 data. This type of action command 33 data function requires 10 data, demands 1 data, directs 3 data, instructs 17 data and requires 2 data. This type of directive prohibition 9 data serves to prohibit 8 data and limit 1 data. The type of action directive given permission 1 data includes enabling. This type of advice action 8 data serves to advise 6 data and suggest 2 data.